Use of Intra-arterial Thrombolytic Therapy for Acute Treatment of Frostbite in 62 Patients with Review of Thrombolytic Therapy in Frostbite. Issue 4 (July 2016) - Gonzaga, Teresa; Jenabzadeh, Kamrun; Anderson, Christopher P.; Mohr, William J.; Endorf, Frederick W.; Ahrenholz, David H.
Abstract : Amputations are common after severe frostbite injuries, often mediated by postinjury arterial thrombosis. Since 1994, the authors have performed angiography to identify perfusion deficits in severely frostbitten digits and treated these lesions with intraarterial infusion of thrombolytic agents, usually combined with papaverine to reduce vasospasm. A retrospective review was performed of patients admitted to the regional burn center with frostbite injury from 1994 to 2007. Patients with severe frostbite, without contraindications to thrombolytic therapy, underwent diagnostic angiography of the affected extremities. Limbs with perfusion defects received intraarterial thrombolytic therapy according to protocol and the response was documented. Delayed amputation was performed for mummified digits. Angiogram results and amputation rates were tabulated. In this 14-year review, 114 patients were admitted for frostbite injuries. There was a male predominance (84%) and the mean age was 40.4 years. Of this group, 69 patients with severe frostbite underwent angiography; 66 were treated with intraarterial thrombolytic therapy. Four treated were excluded due to incomplete data. In the remaining 62 patients, angiography identified 472 digits with frostbite injury and impaired arterial perfusion. At the termination of thrombolytic infusion, a completion angiogram was performed. Partial or complete amputations were performed on only four of 198 digits (2.0%) with distal vascular blush, and in 71 of 75 digits (94.7%) with no improvement. Amputations occurred in 73 of 199 digits (36.7%) with partially restored flow. Overall complete digit salvage rate was 68.6%. Angiography after severe frostbite is a sensitive method to detect impaired arterial blood flow and permits catheter-directed treatment with thrombolytic agents. Improved perfusion after such treatment decreases late amputations following frostbite injury.